Hereditary Spherocytosis: A Case Report - Koju, Surendra; Makaju, Ramesh (Journal of Lumbini Medical College, 2018)
Introduction: Hereditary spherocytosis is a red cell membrane disorder that causes hemolytic anemia. Due to defective cell membrane, red cells are spherical shaped and result in their early lysis. Osmotic fragility of spherocytic red cell is increased. Case report: A 22 year old female presented with chief complain of abdominal pain. Initially she was diagnosed as cholelithiasis. Under laboratory evaluation she was found to be anemic with reticulocytosis. In peripheral blood smear, spherocytes were moderately distributed. Antihuman globulin test was negative but osmotic fragility was high. Hence, she was confirmed as case of hereditary spherocytosis. Conclusion: Hereditary spherocytosis is a rare red cell disorder and its diagnosis can be made by osmotic fragility test. DOI: https://doi.org/10.22502/jlmc.v6i1.202